Analisis Efisiensi Harga pada Pemasaran Bawang Merah di Provinsi Sumatera Barat - Fernando, Zikra; Rosiana, Nia; Priatna, Wahyu Budi (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2025)
West Sumatra is one of the shallot production centers outside Java. In recent years, the price of shallots in West Sumatra has experienced price fluctuations due to oversupply which has an impact on the efficiency of commodity distribution and price stabilization both at the producer level to consumers. Given that shallots are a strategic and high-value commodity, this study aims to analyze the marketing channel to analyze price efficiency in the marketing channel using the price transmission approach. Primary data were obtained through interviews with 100 farmers and 80 marketing institutions while secondary data were daily shallot prices from January 2019 to December 2024. Descriptive analysis was used to identify institutions and marketing channels. To analyze price transmission, the Nonlinear Autoregressive Distributed Lag (NARDL) model was used. The results of the marketing channel analysis show that there are six shallot marketing channels at the level within the province of West Sumatra and three marketing channels with destinations outside the province of West Sumatra. The price transmission analysis with the NARDL model shows that the marketing channels within the province tend to be asymmetric, both in the short and long term. Meanwhile, in channels outside the province, the price relationship between regions generally shows a more symmetrical transmission. Therefore, it can be concluded that shallot marketing in West Sumatra Province has not been price efficient. This study recommends strengthening farmer institutions to increase bargaining power and the role of the government in providing market information systems to make marketing more efficient.